Frequent Leptospira spp. detection but absence of Tula orthohantavirus in Microtus spp. Voles, Northwestern Spain - Jeske, Kathrin; Emirhar, Duygu; García, Jesús T.; González-Barrio, David; Olea, Pedro P.; Fons, Francisco Ruiz; Schulz, Jana; Mayer-Scholl, Anne; Heckel, Gerald; Ulrich, Rainer G. (Journal of Wildlife Diseases, 2021)
The common vole (Microtus arvalis) is a major agricultural pest in Europe and is a reservoir for several zoonotic agents, such as Leptospira spp. and Tula orthohantavirus (TULV). However, little is known about the occurrence of those pathogens in voles from Spain, where the species has largely expanded its distribution range in the past decades, causing agricultural pests and zoonotic diseases. For a molecular survey, 580 common voles and six Lusitanian pine voles (Microtus lusitanicus) were collected in 26 localities from four provinces of northwestern Spain. We assessed the presence of Leptospira spp. DNA in kidney tissue by PCR targeting the lipL32 gene, detecting a prevalence of 7.9% (95% confidence interval, 5.9-10.4) for common voles and of 33.3% (95% confidence interval, 4.3-77.7) for Lusitanian pine voles. We identified Leptospira kirschneri in 24 animals and Leptospira borgpetersenii in two animals, using secY gene-specific PCR. We analyzed environmental and demographic factors (such as age class, weight, and sex) and population dynamics data for their potential effect on the Leptospira spp. prevalence in those voles. The Leptospira spp. DNA detection rate in common voles increased significantly with maximum air temperature, vole weight, and amount of accumulated rainfall during the 90 d before capture and within the peak phase of the population cycle. We assessed the presence of TULV in lung tissue of 389 voles by reverse-transcription PCR, with no positive results. The absence of TULV might be explained by the evolutionary isolation of the common vole in Spain. The detection of two Leptospira genomospecies underlines the necessity for further typing efforts to understand the epidemiology of leptospiral infection in the common vole and the potential risk for human health in Spain.